Menalar Posisi Elit Daerah di Era Demokrasi dan Otonomi Daerah - Hanantyo Sri Nugroho (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
Amid the diverse capacities of local governments in exercising their authority in the era of democracy and regional autonomy, local elites have emerged in the regions. The consequences of the emergence of local elites in the region then gave rise to obstacles in democracy, such as political dynasties as well as conflicts related to control of resources, while the rotational dimensions of power and the welfare of the community began to be marginalized. This can be seen from the strengthening of local strongmen and local bossism. This certainly makes the paradigm confusion associated with local elites and local conflicts that occur in the local post-democratic and regional autonomy regions. As it is known that when the regions have not implemented local autonomy and democracy, what happens is that local elites tend to derivate from national politics so that in the event of local conflict the resolution of the conflict can be more easily resolved. Therefore, it is necessary to return to reasoning to redefine the position of the local elite as a central representation as well as a representation of the local community. This research is qualitative using desk-research. The results show that with local democracy and regional autonomy the spread of political forces makes the formation of local elites that are formed today is centrifugal. DOI: https://doi.org/10.26905/pjiap.v3i1.1989